Self‐report dieting and long‐term changes in body mass index and waist circumference - L. Sares‐Jäske; P. Knekt; S. Männistö; O. Lindfors; M. Heliövaara (Wiley, 2019)
Summary Objective This prospective study explores whether dieting attempts and previous changes in weight predict changes in body mass index (BMI) and waist circumference (WC). Methods The study was based on the representative Finnish Health 2000 Survey and on its follow‐up examination 11 years later. The sample included 2,785 participants, aged 30-69. BMI and WC were determined at health examinations. Information on dieting attempts and previous changes in weight was collected using a questionnaire including questions on whether participant had tried to lose weight (no/yes), gained weight (no/yes) or lost weight (no/yes) during the previous year. Results At baseline, 32.8% were dieters. Of these, 28.4% had lost weight during the previous year. Dieters had higher BMI and WC than non‐dieters. During the follow‐up, the measures increased more in dieters and in persons with previous weight loss. The mean BMI changes in non‐dieters versus dieters were 0.74 (standard deviation [SD] 2.13) kg/m2 and 1.06 (SD 2.77) kg/m2 (P = 0.002), respectively. The corresponding numbers for those with no previous weight change versus those who had lost weight were 0.65 (SD 2.07) kg/m2 and 1.52 (SD 2.61) kg/m2. The increases in BMI and WC were most notable in dieters with initially normal weight. Conclusions The increases in BMI and WC were greater in dieters than in non‐dieters, suggesting dieting attempts to be non‐functional in the long term in the general population.